KINERJA GURU SD DI KECAMATAN SLAWI Suatu tinjauan aspek Persepsi Guru Tentang Kepemimpinan Kepala Sekolah, Budaya Kerja, dan Fasilitas Pembelajaran - Indriasih, Nanik Wahyu (Universitas Muhammadiyah Surakarta, 2013)
The main objectives of this study are 1) to analyze the contribution of teacherâs perception of headmasterâs leadership, job ethics, and learning facilities altogether on state elementary school teacherâs performance in Sub-District of Slawi, 2) to analyze the contribution of teacherâs perception of headmasterâs leadership on state elementary school teacherâs performance in Sub- District of Slawi, 3) to analyze the contribution of job ethics on state elementary school teacherâs performance in Sub-District of Slawi, 4) to analyze the contribution of learning facilities on state elementary school teacherâs in Sub-District of Slawi, and 5) to analyze the variable which dominantly contributes on state elementary school teacherâs performance in Sub-District of Slawi. A quantitative approach is used in this study. The location of the study is in all state elementary schools of Slawi Sub-District, Tegal Regency. Population number of this study are 190 teachers of state elementary schools in Sub-District of Slawi. The sample of this study are 127 teachers selected with a sampling technique based on Isaac and Michaelsâs empiric formula. Data are collected by doing a documentation of library research and using questionnaires. Data are analyzed using regression analysis. Based on data analysis results and previous discussion, it could be concluded that 1) teacherâs perception of headmasterâs leadership, job ethics, and learning facilities simultaneously affect positively and significantly on state elementary school teacherâs performance in Sub-District of Slawi 74.5%. This is shown by acquirement of rest result F with a = 5%. 2) Teacherâs perception of headmasterâs leadership partially contributes positively on teacherâs performance of state elementary schools in Sub-District of Slawi 8.78%. This is shown by acquirement of rest result t with a = 5%. 3) Job ethics partially contributes positively on teacherâs performance in Sub-District of Slawi 59.54%. This is shown by acquirement of rest result t with a = 5%. 4) Learning facilities partially contributes positively on teacherâs performance of state elementary schools in Sub-District of Slawi with 6.20%. This is shown by acquirement of rest result t with a= 5%. 5) Result of assumption test classical indicates that regression model do not experience of classic assumption problem or diffraction so that can be expressed by BLUE (Best, Linear, Unbiased, and Estimator).